English Teachers’ Perception of Merdeka Curriculum Implemetation - Defriani Waruwu (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2024)
The Merdeka curriculum is a crucial tool for educational systems, as it guides teaching and learning processes and measures progress. This study aims to understand English teachers' opinions on the Merdeka curriculum, and the responses were analyzed using qualitative methods. English teachers have expressed differing opinions about the learner-centered Merdeka curriculum. Due to limited resources and the curriculum's recent introduction, a few educators had difficulties putting it into practice. They did, however, recognize the curriculum's potential advantages, such as student autonomy and joyful learning. They also emphasized the significance of infrastructure and facility availability, as well as the competency, abilities, and mindset of educators. Notwithstanding these difficulties, educators saw chances for assistance from parents, curriculum teams, and principals in addition to the beneficial application of technology in the classroom. All things considered, there is potential for growth as well as obstacles with the Merdeka curriculum.